Visceral Debranching for the Treatment of Thoracoabdominal Aortic Aneurysms - Damrauer, Scott M. (Science International Corporation, 2015)

(untitled) (Aorta (Stamford))
Surgical repair of thoracoabdominal aortic aneurysms (TAAA) is associated with significant morbidity and mortality. Hybrid approaches that involve visceral debranching and aortic endografting allow for an alternative approach in certain high-risk patients. In most circumstances the visceral vessels can be bypassed in a retrograde manner from the iliac arteries via a midline laparotomy, and the aortic aneurysm subsequently excluded with standard aortic endografts. These procedures avoid the extensive two-cavity exposure, aortic cross-clamping, and mechanical circulatory support that comprise open TAAA repair, and offer the theoretical advantage of being less invasive. Despite this, outcomes have been mixed with reported perioperative mortality rates of 0% and 34% and permanent paraplegia rates of 0% to 13% in most major series. The reported outcomes, as well as the variation between centers, highlight the importance of patient selection in undertaking hybrid repair. In practice, the best outcomes are achieved in patients who have high-risk anatomy, rather than high-risk comorbidities.